Berberis aristata: An Endangered High Value Medicinal Shrub of Western Himalayas in Peril - Malik, A. R.; Tariq, Nisha; Sofi, P. A.; Singh, Amerjeet; Peerzada, Ishtiyak Ahmad; Mushtaq, Tahir; Pala, N. A.; Butola, J. S.; Ayoob, Bilkees (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
Berberis aristata DC. commonly known as “Daru haldhi and Chitra” is a spinous shrub native to the northern Himalayan region. The plant is widely distributed from the Himalayas to Srilanka, Bhutan and Jammu and Kashmir. It is mainly propagated through seeds, self-sown in nature. Propagation through cuttings has also been reported. Berberis aristata has been used in Ayurvedic medicines for a long time. The plant is used traditionally in inflammation, wound healing, skin disease, jaundice and infection of the eyes. The berries are edible and rich in vitamin C. A highly valuable Ayurvedic preparation ‘Rasaut’ is prepared from the root of the plant and is used in curing human ailments like ophthalmic, ulcers as a laxative, tonic and blood purifier. High demand for local usage as well as for pharmaceuticals creates serious pressure on the plant which already categorized the plant as an “endangered” species per (IUCN) criteria. Phytochemical studies show that the plant B. aristata contains mainly yellow colored Berberine, oxyberberine, berbamine, aromoline and palmatine. The plant has effective pharmacological action and shows a promising future for further researchers.